A case report of epiploic appendagitis as a mimic of acute cholecystitis. (2018) - Chan, Emily; El-Banna, Alaa
Highlights: Epiploic appendagitis can mimic acute cholecystitis and other common causes of abdominal pain. Epiploic appendagitis should be included in the differential of acute abdominal pain. Epiploic appendagitis is initially managed conservatively with analgesia and anti-inflammatories. Abstract: Introduction: Epiploic appendagitis is a rare cause of acute abdominal pain. It's presentation often mimics other causes of acute abdominal pain. It is important for clinicians to be aware of an epiploic appendagitis since a delay in diagnosis can lead to unnecessary hospital stay, antibiotic usage and surgical intervention [1–4 ]). We present a case of epiploic appendagitis mimicking acute cholecystitis in a rural community hospital. Case report: A 54 Caucasian male self-presents to the emergency department on a Saturday with severe right upper quadrant pain. He was initially diagnosed as acute cholecystitis and managed with antibiotics. Due to limitations with out-of-hours radiology, an ultrasound (US) scan was performed two days after admission. This US showed no evidence of cholecystitis or gallstones. A computed tomography (CT) scan was subsequently performed which revealed a diagnosis of epiploic appendagitis. The patient was discharged with analgesia and anti-inflammatories. Discussion: Epiploic appendagitis can mimic common pathologies causing acute abdominal pain. Unlike its mimics, epiploic appendagitis is a self-limiting condition and its initial management remains conservative. It is diagnosed with imaging studies such as CT scans. It is important for clinicians to be aware of an epiploic appendagitis as a cause for abdominal pain since a delay in diagnosis can lead to unnecessary hospital stay, antibiotic usage and surgical intervention [1–4 ]. Conclusion: A diagnosis of epiploic appendagitis should remain on the list of differential diagnosis for acute abdominal pain. A prompt diagnosis of epiploic appendagitis avoids unnecessary surgical intervention and antibiotic usage.